2011
DOI: 10.1177/0892705711420595
|View full text |Cite
|
Sign up to set email alerts
|

Ductile–brittle transition temperature of polylactic acid-based biocomposite

Abstract: Almost all materials exhibit sensitivity of mechanical properties to temperature. Polylactic acid (PLA), an amorphous polymeric material, also exhibits this type of behavior. Because of its limited application in structural purpose, very few journals and articles study the ductile-brittle transition temperature (DBTT) of polymeric materials, especially PLA. It is necessary to determine DBTT to avoid brittle and catastrophic failure. This article determined the ductile-to-brittle transition of various PLA-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…Moreover, XPS survey spectra ( Figure 5 ) and FTIR showed the presence of Na as sodium carboxylate on the surface of MCC-T which may catalyze the depolymerization reaction of PHB. Indeed, previous study has shown that many metal compounds but especially Na and Mg accelerate the random chain scission and the degradation of PHB [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, XPS survey spectra ( Figure 5 ) and FTIR showed the presence of Na as sodium carboxylate on the surface of MCC-T which may catalyze the depolymerization reaction of PHB. Indeed, previous study has shown that many metal compounds but especially Na and Mg accelerate the random chain scission and the degradation of PHB [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…The more accentuated decrease of the E’ , observed between about −10 °C and 25–30 °C, was determined by the transition of PHB from glassy to rubbery state and the activation of molecular segmental motions at the glass transition temperature [ 44 ]. Variation of loss factor (tan δ) with temperature ( Figure 10 b) emphasizes the relative contributions of the elastic and viscous components when temperature increases.…”
Section: Resultsmentioning
confidence: 99%
“…During the impact test, the energy absorbed from the fracture of the specimen was calculated by using Equation (1). Likewise, the Charpy impact strength can be calculated by dividing the absorbed energy by the cross-sectional area to determine the DBTT [15]. Experimental temperatures set for specimens were in the range between the RT (room temperature) and CT (−160 °C).…”
Section: Resultsmentioning
confidence: 99%
“…With the decreased temperature, the chain in the polymer is rigidly bounded. In these circumstances, the absorbed impact energy was demonstrated to decrease [15].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation